PENAMPILAN KARAKTER FENOTIPIK 15 GALUR INBRED JAGUNG SELFING KE-14 (S-14) RAKITAN POLINELA - Kartahadimaja, Jaenudin; Syuriani, Eka Erlinda (JURNAL AGROTROPIKA, 2013)
To produce F1 hybrid seed corn, it need seed parent strains or known as a superior inbred strains. The purpose of the study was to determine the character of phenotypic and yield potential of 15 maize inbred lines of 14th selfing generations (S - 14) as a prospective parent of hybrid corn assemblied by Polinela. The study was conducted with Randomized Block Design ( RCBD ), each treatment was repeated three times. Data were analyzed by analysis of variance. If there is a difference between the treatment then it continued with Test Honestly Significant Difference ( HSD ) at the 5% level. The results showed that phenotypic characters and the potential results of 15 strains of inbred corn has diverse variability .  Key words: Corn, hybrid, inbred strains, phenotypic